What do beginning teachers make of task-based language teaching? A comparative re-production of East (2014). (October 2021) - East, Martin
Abstract: East (2014) presented a largely qualitative study that uncovered how beginning teachers of languages other than English developed their understandings about task-based language teaching (TBLT) as they took part in a year-long initial teacher education programme in New Zealand. This paper reports a comparative re-production. It complements a recent New Zealand based study, experimental in nature, and its approximate replication (Erlam & Ellis, 2018a, b). The present paper argues that TBLT remains in practice a contested endeavour. Positive experimental research findings are not necessarily finding their way into classrooms, and practitioner-focused studies play a crucial role in adding to our knowledge of what works and what does not work in authentic contexts. The original study and the comparative re-production addressed the same research questions and drew on parallel data sources. The findings of the comparative study, which supported those of the original study, helped in identifying more clearly the issues at stake for the profession and the variables that require attention. It is apparent that the challenges reside in upskilling and supporting practising teachers, who need to become a stronger focus of dedicated and long-term professional development opportunities that will introduce them to the innovation, and sustain them in its implementation.